2009
DOI: 10.1007/s11664-009-0922-0
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effect on Intermetallic Compound Growth Kinetics of Cu Pillar/Sn Bumps

Abstract: The in situ intermetallic compound (IMC) growth in Cu pillar/Sn bumps was investigated by isothermal annealing at 120°C, 150°C, and 180°C using an in situ scanning electron microscope. Only the Cu 6 Sn 5 phase formed at the interface between the Cu pillar and Sn during the reflow process. The Cu 3 Sn phase formed and grew at the interfaces between the Cu pillar and Cu 6 Sn 5 with increased annealing time. Total (Cu 6 Sn 5 + Cu 3 Sn) IMC thickness increased linearly with the square root of annealing time. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 18 publications
(20 reference statements)
0
22
1
Order By: Relevance
“…This differs from earlier published work, which considered IMC formation to be fully diffusion controlled, [18][19][20][21][22] with an analytical solution of the diffusion equation of n = 1/2. However, several studies have presented values of n that vary with temperature.…”
Section: Kinetics Model Estimationcontrasting
confidence: 71%
“…This differs from earlier published work, which considered IMC formation to be fully diffusion controlled, [18][19][20][21][22] with an analytical solution of the diffusion equation of n = 1/2. However, several studies have presented values of n that vary with temperature.…”
Section: Kinetics Model Estimationcontrasting
confidence: 71%
“…Currently, the research activities of Cu-In system mainly focus on Cu-In intermetallic compounds theoretical analysis and their growth kinetics [14][15][16][17]. However, there is a lack of systematic study on microstructure evolution of Cu/In/Cu joints under different bonding conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,18 Cu 3 Sn layers on both interfaces grew to similar thickness. The growth rate of Cu 3 Sn in Cu pillar/Sn bumps was also faster than that of Cu 6 Sn 5 due to the Sn-limited nature of the Cu-Sn reaction system, 11,19 while in a conventional solder bump the Cu-Sn reaction system is Cu limited. The Sn phase was not observed at the Cu pillar/Sn interface after 165 h at 150°C or after 100 h at 150°C, 3.5 9 10 4 A/cm 2 ; on the other hand, the Sn phase was still observed at the Cu pillar/Sn interface after 360 h at 100°C.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results are reported elsewhere. [11][12][13] Kirkendall voids were observed at the Cu/Cu 3 Sn interface as well as within the Cu 3 Sn layer. It has been reported that the Kirkendall void formation mechanism can be ascribed to the different diffusivities of Cu and Sn.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation